Usability Evaluation Using Heuristic Method Against NELPIN Website - Zaidan Husin; Wenny Eka Maulitya; Sifa Urrohmah (Institute of Computer Science (IOCS), 2022)
The wealth of marine resources in Indonesia is known to be very abundant, especially in fishery products, but until now many fishermen have not been maximal in carrying out fishing activities. Therefore, related parties have launched the NELPIN website which can make it easier for fishermen to carry out fishing activities. To prove that the website can provide convenience to its users, it is necessary to evaluate the usability to test the NELPIN website using the Heuristic method. The system itself needs to be evaluated so that it can be seen whether the system is functioning as desired and errors or deficiencies in the system can be identified and corrected as quickly as possible. The data from this research will be obtained from filling out a questionnaire containing questions regarding usability aspects to evaluate whether the NELPIN website provides convenience for its users or not. Then the results of filling out this questionnaire will be analyzed to draw conclusions and the researchers will provide suggestions that the NELPIN website development team might use to make improvements to the usability of the website.